1967
DOI: 10.1113/jphysiol.1967.sp008258
|View full text |Cite
|
Sign up to set email alerts
|

The demonstration of luteinizing hormone releasing factor in hypophysial portal blood of pro‐oestrous and hypophysectomized rats

Abstract: SUMMARY1. A method for the routine collection of hypophysial portal blood from rats under direct vision has been described.2. This method has been used to obtain portal blood from adult female rats in pro-oestrus and adult female rats which had been hypophysectomized at least 14 days before collection.3. The pooled plasma from this blood was assayed for activity, resembling that of luteinizing hormone releasing factor (LRF), by the ovarian ascorbic acid depletion method.4. The portal plasma from both groups of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1968
1968
2007
2007

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Effect of electrical stimulation of the preoptic area on LH-RF in jugular venous and 'pharyngeal' blood in pro-oestrous rats These experiments were carried out to determine whether the amount of immunoreactive LH-RF in pituitary stalk blood is greater than in jugular venous or 'pharyngeal' blood. The experimental design was similar to that described by Fink et al (1967; Table 5). Seven female rats which had exhibited regular 4-day cycles and in which electrodes had been implanted in the medial preoptic area were anaesthetized with urethane at pro-oestrus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of electrical stimulation of the preoptic area on LH-RF in jugular venous and 'pharyngeal' blood in pro-oestrous rats These experiments were carried out to determine whether the amount of immunoreactive LH-RF in pituitary stalk blood is greater than in jugular venous or 'pharyngeal' blood. The experimental design was similar to that described by Fink et al (1967; Table 5). Seven female rats which had exhibited regular 4-day cycles and in which electrodes had been implanted in the medial preoptic area were anaesthetized with urethane at pro-oestrus.…”
Section: Resultsmentioning
confidence: 99%
“…With the aid of a number of different bioassay systems it was shown that pituitary stalk blood collected by this method possesses the capacity to release luteinizing hormone (LH) (Fink, Nallar & Worthington, 1967; decapeptide, (Pyro) Glu-His-Trp-Ser-Tyr-Gly-Leu-Arg-Pro-Gly-NH2, isolated from por¬ cine (Matsuo, Baba, Nair, Arimura & Schally, 1971) and ovine (Burgus, Butcher, Amoss, Ling, Monahan, Rivier, Fellows, Blackwell, Vale & Guillemin, 1972) hypothalamic extracts is by far the most potent. It is possible to raise antisera to the unconjugated (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A hole was then drilled in the frontal bone and a concentric bipolar stimulating electrode (Type SNEX-100; Rhodes Medical Instruments Ltd, Los Angeles, California, U.S.A.) lowered into the preoptic and/or anterior hypothalamic areas (PO/AH; anterior 6-8, lateral 008, depth 8-25; König & Klippel, 1963). The stereotaxic instrument was then inverted to present the ventral aspect of the rat and permit exposure of the median eminence and pituitary stalk by a transpharyngeal approach (Fink, Nallar & Worthington, 1967;). A small hole was cut in the dura with an iridectomy knife and a non-concentric bipolar stimulating electrode (Type SNEX-200; Rhodes Medical Instruments Ltd) was placed on the median eminence so that one pole rested on the mid-line and the other ipsilateral with the PO/AH electrode.…”
Section: Methodsmentioning
confidence: 99%
“…The technique of Worthington (1966), Fink, Nallar & Worthington (1967) and Porter & Smith (1967) was rigidly followed, except that no heparin was injected and that the animal received no blood infusion. With a dental drill, CaCl2 or MgCl2 and ADH release 85 a hole was made in the bone to expose the dura mater between the posterior margin of the optic chiasma and the pons.…”
Section: Methodsmentioning
confidence: 99%